Characterization and evaluation of a novel semi-industrial scale vertical shaft furnace for particle spheroidization. Issue 3 (June 2020) - Knoll, M.; Gerhardter, H.; Prieler, R.; Hochenauer, C.; Mühlböck, M.; Tomazic, P.; Schröttner, H.
Abstract: In this study, a novel furnace concept for in-flight particle spheroidization is presented, characterized and evaluated. A natural gas fired burner with a continued staged air principle and internal recirculation (COSTAIR), was used to provide the required temperature for the spheroidization process. Therefore, a numerically inexpensive CFD model for the calculation of combustion and multiphase flow is proposed. Particularly for the calculation of particle trajectories and particle peak temperatures of non-spherical (chiseled and flaky) slag particles, the presented CFD model differs in two modifications from the current state-of-the-art CFD models: first, a numerically efficient combustion model with a detailed chemical reaction mechanism was used in order to calculate the temperature profile of the furnace. While in most current state-of-the-art CFD models the numerically expensive and time consuming eddy dissipation concept (EDC) model or the insufficient eddy dissipation model (EDM) are used. Second, the discrete phase model, which is based on a numerically efficient Euler-Lagrangian approach, is used for multiphase modeling. Non-spherical particles are considered by application of a suitable particle drag model from literature. Although, the assumption of spherical particles is more common in current state-of-the-art CFD models for multiphase modeling. It was concluded that the presented furnace concept is applicable for the semi-industrial scale production of spherical boiler slag particles. The numerical results show that the assumption of non-spherical particles, compared to spherical particles, is more suitable for the calculation of particle trajectories and particle peak temperatures in the presented furnace. Highlights: A novel furnace concept for particle spheroidization is presented. Time saving combustion modelling using a flamelet approach. Characterization of temperature and flow conditions in the furnace. Application of a numerically inexpensive Euler-Lagrangian approach. Comparison between CFD and measurements.